2012
DOI: 10.1007/s00709-012-0417-3
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and molecular characterization of a putative bZIP transcription factor VvbZIP23 from Vitis vinifera

Abstract: The proteins harboring bZIP domains comprise a large family and play key roles in many cellular processes, one of them being tolerance to biotic and abiotic stresses in plants. In the present study, we characterize a putative bZIP transcription factor from Vitis vinifera namely VvbZIP23. Our studies revealed that a GFP fusion of VvbZIP23 is localized in the nucleus showing VvbZIP23 codes for a nuclear localized protein. VvbZIP23 identified by in silico approaches from grapevine DNA databases available in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Additionally, it has been shown that A. thaliana over-expressing wheat bZIP60 exhibits increased drought, salt and freezing tolerance . However, to date there is only one report that has addressed the function of a bZIP gene from grapevine (Tak and Mhatre 2013), one of the most economically important perennial fruit crops globally, due to its diverse uses, including the production of wine, jam, juice and jelly, grape seed extracts, raisins, vinegar, and grape seed oil. Since the production of grape is limited by a range of biotic and abiotic stresses, which cause significant losses in yield every year, as well as a reduction in berry quality (Ferreira et al 2004), the expression and function of grape regulatory gene families is of considerable interest.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, it has been shown that A. thaliana over-expressing wheat bZIP60 exhibits increased drought, salt and freezing tolerance . However, to date there is only one report that has addressed the function of a bZIP gene from grapevine (Tak and Mhatre 2013), one of the most economically important perennial fruit crops globally, due to its diverse uses, including the production of wine, jam, juice and jelly, grape seed extracts, raisins, vinegar, and grape seed oil. Since the production of grape is limited by a range of biotic and abiotic stresses, which cause significant losses in yield every year, as well as a reduction in berry quality (Ferreira et al 2004), the expression and function of grape regulatory gene families is of considerable interest.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, bZIP genes are important regulators of many stress conditions. To date, only a few grapevine bZIP TF has been characterized (Tak and Mhatre 2013), and its role in stress responses has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…glycinea, indicating post-translational control of G/HBF-1 (Dröge-Laser et al 1997). In grapes, a bZIP member called VvbZIP23 has been identified as a key regulator of stress responses, and its expression is strongly induced by drought, salinity, cold, abscisic acid, ethylene, jasmonic acid (JA), and SA (Tak and Mhatre 2012). A translation factor named PPI1, which has a different structure to other previously studied bZIPs, was characterized in peppers (Lee et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Since Vitis is sister to all Rosids (I and II), studying the evolution of a large gene family in grapevine will shed light on our understanding the evolution of other plants [36], and will allow the elucidation of function and divergence of gene families in grapevine. So far, only a limited number of VvbZIPs have been isolated and functionally characterized [37]. Among them, two VvABF s (homologous of VvbZIP08 and VvbZIP45 in our study), isolated from the V. vinifera cultivar ‘Thompson Seedless’ , were induced by various abiotic stresses including drought, salinity, cold and the exogenous hormone ABA [38], and VvbZIP45 corresponds to the very recently described ABSCISIC ACID RESPONSE ELEMENT-BINDING FACTOR2 ( VvABF2 ), involved in ABA-dependent grape berry ripening [39].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, two VvABF s (homologous of VvbZIP08 and VvbZIP45 in our study), isolated from the V. vinifera cultivar ‘Thompson Seedless’ , were induced by various abiotic stresses including drought, salinity, cold and the exogenous hormone ABA [38], and VvbZIP45 corresponds to the very recently described ABSCISIC ACID RESPONSE ELEMENT-BINDING FACTOR2 ( VvABF2 ), involved in ABA-dependent grape berry ripening [39]. Another gene, VvbZIP23 , which was isolated from the cultivar ‘Mango’ , was induced by a wide spectrum of abiotic stresses, including drought, salt, cold, and application of abscisic acid, methyl viologen, salicylic acid, jasmonic acid, and ethephon [37]. In addition, the transcriptional analysis of late ripening stages of grapevine berry detected one bZIP transcription factor which exhibited lower expression at the harvest stages (TH) than that at the 7-days before harvest stage (TH-7) [40].…”
Section: Introductionmentioning
confidence: 99%